[68Ga]Ga-DOTA-TATE uptake in subacute stroke following craniotomy for meningioma: a diagnostic tool for stroke?. Issue 4 (29th April 2022) - Cappuzzo, Justin; Popoola, Daniel; Prasad, Dheerendra; Lipinski, Lindsay
Abstract : Gallium 68 ( 68 Ga) 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid labelled octreotate ([ 68 Ga]Ga-DOTA-TATE) positron emission tomography (PET) is an established imaging technique for identifying tumours of neuroendocrine origin and meningiomas; the radiotracer binds to somatostatin receptor type 2 (SSTR2), which is richly expressed by these malignancies. Here, we present a rare case hinting at novel ischaemic stroke detection by [ 68 Ga]Ga-DOTA-TATE PET scan. The scan was performed 14 days post resection of an atypical meningioma with the intention to assess the extent of residual tumour for radiosurgical treatment of the operative cavity. Surprisingly, the [ 68 Ga]Ga-DOTA-TATE PET-avid region corresponded to an area of perioperative subacute ischaemic stroke detected by MRI. This case corroborates the two previously reported cases of incidental detection of ischaemic stroke during routine [ 68 Ga]Ga-DOTA-TATE PET imaging, collectively suggesting the need for caution when interpreting the imaging findings. A possible underlying mechanism for [ 68 Ga]Ga-DOTA-TATE uptake in stroke is increased SSTR2 expression by macrophages recruited into infarcted tissue.